2001
DOI: 10.1103/physrevlett.86.4009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of Spatial Antibunching of Photons

Abstract: We report an interference experiment that shows transverse spatial antibunching of photons. Using collinear parametric down-conversion in a Young-type fourth-order interference setup we show interference patterns that violate classical Schwarz inequality and should not exist at all in a classical description.Photon antibunching in a stationary field is recognized as a signature of nonclassical behavior, for its description is not possible in terms of a nonsingular positive GlauberSudarshan P distribution [1]. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 11 publications
1
49
0
Order By: Relevance
“…In the same spirit, the anti-bunching of photons was later demonstrated in the transverse spatial domain in Ref. [18], and was probably the first formal demonstration of the non-classical behavior of spatial correlations. In 2004, Howell et al [21] and D'Angelo et al [22] demonstrated that the pairs of down-converted photons are indeed entangled by experimentally violating classical separability criteria.…”
Section: Spatial Correlations: Quantum Versus Classicalmentioning
confidence: 83%
See 4 more Smart Citations
“…In the same spirit, the anti-bunching of photons was later demonstrated in the transverse spatial domain in Ref. [18], and was probably the first formal demonstration of the non-classical behavior of spatial correlations. In 2004, Howell et al [21] and D'Angelo et al [22] demonstrated that the pairs of down-converted photons are indeed entangled by experimentally violating classical separability criteria.…”
Section: Spatial Correlations: Quantum Versus Classicalmentioning
confidence: 83%
“…A more comprehensive study of these far field correlations were made by Grayson and Barbosa [10]. Experiments exploring interference at a double slit experiment using twin photons and coincidence counting came in 1994 [13] and 1995 [14] and was further investigated in later work [50,34,19,17,51,52,53,18,54,55]. In this section, we review some of the key experiments exploring aspects of interference of photon pairs using a double slit.…”
Section: Double Slit Experiments With Twin Photonsmentioning
confidence: 99%
See 3 more Smart Citations